Through a sober lens : a photographers journey /| - Blanchard, Michael (Photographer) (West Tisbury, MA : Genevieve Press, 2019)
"By blending photography and writing Michael provides insight into the diseases of alcoholism and addiction and the pathways to recovery. In this new collection of photographs and essays he shares stories of resilience, compassion and empathy. Michael reveals candid details of his own journey, from his three month stay at the Talbot recovery campus in Atlanta to a new life filled with caring and connection. Along the way he discovers that sobriety is more than the absence of alcohol - its the presence of love, hope, faith and contribution. Through his interactions with fellow souls on the healing journey he learns that, in his own words: We are never alone."--Publisher
Keywords: Blanchard, Michael -- (Photographer); Landscape photography; Recovering alcoholics -- Rehabilitation -- United States; Photobooks; Essays; Anecdotes